(untitled) (Revista Direito em Debate, 2020)
This article discusses the legal requirement to register a technology transfer and franchise contract with the National Institute of Industrial Property (INPI). The paper looks at issues related to legal uncertainty, the excess of bureaucracy generated, the relationship of the issue with the Brazilian System of Economic Defense and the inexistence of this reality in other legal systems of countries of greater international importance. Finally, such bureaucratic procedures are now subject to criticism from the viewpoint of adopting measures compatible with Brazil’s degree of economic openness, understanding that this legal requirement contributes to the so-called “Brazil Cost”.